Comparative genomics of cell wall remodelling genes in fleshy fruit species and the control of fruit softening in tomato - Samsulrizal, Nurul Hidayah; Fray, Rupert; Seymour, Graham B (2017)
Fruits are the seed dispersal units of flowering plants and fleshy fruits form an important part of the human diet. Ripening is a complex developmental process and involves many events such as textural and constitutional changes. The texture of fleshy fruits is one of the major criteria for consumer choice. However, the molecular determinants of ripening- associated changes in texture or “softening” are relatively poorly understood and seem to involve a large number of cell wall remodelling factors. The recent completion of the tomato genome sequence has revealed more than 50 cell wall structure-related genes that are expressed during fruit development and ripening and may impact texture changes in this fruit (Tomato Genome Consortium, 2012). Also expression of these genes appears to be under both genetic and epigenetic control. The aim of the project is to compare, on a genome-wide scale, ripeningrelated gene expression in a range of fleshy fruits and especially those linked with cell wall remodelling. Then by identifying orthologous genes in different fruit species to make predictions about those genes likely to important for the softening process in all fleshy fruits. We hypothesise that there is a core set of genes that is always associated with fruit softening. Several software have been used in this study such as Inparanoid, SyMAP and OrtoMCL.Comparative genomics analysis of tomato (Solanum lycopersicum), banana (Musa acuminate), melon (Cucumis melo) and grape (Vitis vinifera), has been undertaken using Inparanoid software. This analysis showed that a total of 8,982 (25.86%) gene models could be identified in common between all four genomes based on comparison of amino acid sequences. Of these 8,982 genes, 262 in tomato, 252 in grape, 261 in melon, and 198 in banana were identified as encoding cell wall structure-related proteins. However, comparison of the expression patterns of these genes revealed that most were expressed in tissues other than ripening fruits, and of the fruit expressed genes only a small number were common between different fruit species. This in silico analysis should provide additional clues as to genes to target for manipulation of fruit softening in a range of fleshy fruit species. These also provide new opportunities to develop varieties of tomatoes that can survive the trip from the farm to the grocery store whilst maintaining excellent flavour and shelf-life